Caste Conflicts and Children’s Education† - Ajay Kumar Singh, (THE PRIMARY TEACHER, 2025)
Caste conflicts continue to structure the public arena in India, as also reflected in the recent controversy over Ambedkar cartoons in NCERT textbooks or in the demand for reservation by Gurjars in Rajasthan which once again brought the issue into the limelight. At least in the Hindi speaking region, the repertoire of caste conflicts appears to be powerful, while the apparent conflict is relatively 'silent'. The crystalisation of caste identities has raised some important questions on the socio-cultural and educational cleavages of Indian society. The impact of conflict on children and its relationship to their education process continues to be one of the most critical areas in research, especially in India. The present study tries to explore the relationship between experiences of conflict and children's education with special focus on caste conflict. A hierarchical relationship between the adults and children provides a guideline for the study